Research progress on causes and nursing countermeasures of falls in elderly stroke patients (老年脑卒中患者跌倒原因分析与护理对策研究进展) - MA Cuiqing (马翠卿); YANG Mei (杨梅) (中西医结合护理)
Falls are one of the most common adverse events resulting in physical and mental harm of stroke patients. This paper reviewed researches on causes and nursing countermeasures of fall in elderly stroke patients, and provided reference for reducing fall risk and ensuring safety of elderly stroke patients during treatment. (脑卒中患者跌倒是临床常见不良事件, 严重危害患者身心健康。本研究就导致脑卒中患者跌倒的主要原因素以及护理对策进行总结, 旨在为临床工作中进一步降低老年脑卒中患者跌倒不良事件的发生、保障患者生命安全提供参考。)